2020
DOI: 10.21203/rs.3.rs-61612/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Association of depression symptom severity with short-term risk of an initial hospital encounter in adults with major depressive disorder

Abstract: Background: Despite the availability of pharmacologic and nonpharmacologic treatment options, depression continues to be one of the leading causes of disability worldwide. This study evaluated whether depression symptom severity, as measured by PHQ-9 score, of patients diagnosed with MDD is associated with short-term risk of a hospital encounter (ER visit or inpatient stay). Methods: Adults with ≥1 PHQ-9 assessment in an outpatient setting (index date) and ≥1 MDD diagnosis within 6 months prior were included f… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Further, a study by Voelker et al. (34) found that depression symptom severity is associated with increased risk of all‐cause and MDD‐related hospital encounters. A meta‐analysis by Zhou et al.…”
Section: Discussionmentioning
confidence: 99%
“…Further, a study by Voelker et al. (34) found that depression symptom severity is associated with increased risk of all‐cause and MDD‐related hospital encounters. A meta‐analysis by Zhou et al.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the severity of depressive symptoms in major depressive disorder (MDD) was reported to be associated with an increased risk of an MDD-related hospital encounter in the short term (13). A recent study showed that patients with MDD and suicidal ideation (vs patients without suicidal ideation and the general population) had significantly worse quality of life, high healthcare resource use, and greater loss of productivity and impediment of activity (14).…”
Section: Introductionmentioning
confidence: 99%